Formulation and Evaluation of Azelnidipine Solid Lipid Nanoparticles - Gugulothu, Bhaskar; Chinthala, Praveena (Journal of Neonatal Surgery, 2025)
Introduction: Azelnidipine is a third-generation, long-acting dihydropyridine calcium channel blocker used to treat high blood pressure. The aim of the study was to prepare Azelnidipine solid lipid nanoparticles (SLN) to improve the solubility and bioavailability. Methods: Six SLN formulations F1-F6of Azelnidipine were developed using three different lipids - Trimyristin, Tripalmitin and Tristearin at varying concentrations by the hot homogenization followed by ultrasonication method. All the formulations were characterized for their particle size (Ps), zeta potential (ZP), entrapment efficiency (EE), assay and drug release. The stability study test was conducted on optimized formulation at room temperature and refrigerated conditions for 3 months. Results: The particle sizes of the formulations ranged from 167 ± 2.1 to 325 ± 1.3 nm, with PDI values between 0.267 ± 0.03 and 0.384 ± 0.03. Zeta potential ranged from –18.17 ± 1.1 to –23.01 ± 1.3 mV, and entrapment efficiency was between 84.21 ± 0.1% and 94.16 ± 0.1%. In vitro drug release studies, conducted using the dialysis method in 0.1 N HCl and pH 6.8 phosphate buffer, demonstrated a slower release in acidic medium compared to the phosphate buffer. Among all formulations, F5 prepared with Tripalmitin exhibited the highest drug release of 79.21% over 24 hours in pH 6.8 phosphate buffer. Based on particle size, entrapment efficiency, and drug release profile, F5 was selected as the optimized formulation. Stability studies confirmed that F5 remained stable for at least three months. Conclusion: The optimized formulation (F5) demonstrated the highest zeta potential, excellent entrapment efficiency, small particle size, and sustained drug release over 24 hours, indicating that SLN are a promising delivery system for enhancing the bioavailability of Azelnidipine.